VOICE CONTROLLED ROBOTIC ARM - P Naik, Adwait (IAES International Journal of Robotics and Automation (IJRA), 2020)
Robotic arms are programmable mechanical manipulators with movable components which can cause relative motion between adjoining links. The aim of this project is developing a robotic arm capable of identifying the voice commands. The speech acts as an input responsible for triggering action. Apart from having diverse applications in industries, with advancement in technology and medical sciences, the robotic prosthesis is highly successful at restoring one's biological ability to perform daily chores comfortably. This approach commits to a goal to accomplish a well-built system with minimum faults. Computing coordinates to attain a Soft-home position is an essential task which is responsible for achieving the required speed, torque, and delivers optimum performance. Most challenging part in the whole procedure is to obtain high calibration for smooth working of the arm. We have employed a software-based calibration technique which is simple to implement and highly efficient.